Anion exchange resin removal of per- and polyfluoroalkyl substances (PFAS) from impacted water: A critical review. (15th July 2021) - Boyer, Treavor H.; Fang, Yida; Ellis, Anderson; Dietz, Rebecca; Choi, Youn Jeong; Schaefer, Charles E.; Higgins, Christopher P.; Strathmann, Timothy J.
Highlights: Polyacrylic AER and short-chain PFCAs and PFECAs favor electrostatic interactions Polystyrene AER and long-chain PFAS including neutral FASAs combine interactions AER selectivity for PFAS: PFBA < PFHxA < GenX < PFBS < PFOA ≈ PFHxS ≈ FOSA < PFOS Column studies show better removal of short-chain PFAS using polystyrene/gel AER Weak-base AER best candidate for aqueous-only regeneration and desorption of PFAS Graphical abstract: Image, graphical abstract Abstract: A key gap in the literature on the treatment of per- and polyfluoroalkyl substances (PFAS) in impacted water is the absence of a review article dedicated to anion exchange resin (AER) treatment. This gap is important because previous research has consistently shown adsorption by AER to be one of the most effective treatment processes for PFAS removal from impacted water, and AER is one of the most commonly deployed technologies in the field. Given the scope of the previous review articles on PFAS removal by various adsorbent types, the sections on AER do not explore the full depth of PFAS and AER interactions nor cover the breadth of AER testing conditions. Accordingly, the goal of this paper was to critically review the available peer-reviewed literature on PFAS removal from water by AER. The specific objectives of the review were to synthesize the previous literature results on (1) batch adsorption behavior, (2) impact of water chemistry conditions, (3) continuous-flow adsorption, (4) adsorption modeling, (5) regeneration, and (6) weak-base AER. Following from critical review of the literature, the future research priorities discussed include: (i) improving the underlying science that governs PFAS–resin interactions, (ii) improving methods for resin regeneration and management of PFAS-contaminated concentrate streams, and (iii) comparative life cycle environmental and economic analyses for ion exchange treatment systems relative to competing technologies.